2006
DOI: 10.1007/s00414-006-0124-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation of 52 new Y-STR loci in the Y Chromosome Consortium worldwide panel of 76 diverse individuals

Abstract: We have established 16 small multiplex reactions of two-four loci to amplify 52 recently described singlecopy simple Y-STRs and typed these loci in a worldwide panel of 74 diverse men and two women. Two Y-STRs were found to be commonly multicopy in this sample set and were excluded from the study. Of the remaining 50, four (DYS481, DYS570, DYS576 and DYS643) showed higher diversities than the commonly used loci and can potentially provide increased haplotype discrimination in both forensic and anthropological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 11 publications
(17 reference statements)
0
22
0
Order By: Relevance
“…We investigated a Chinese family carrying the DFNY1 Y-linked hearing-impairment mutation [6] and genotyped two family members, DFNY1-66 (affected) and DFNY1-101 (unaffected), who were separated by 13 generations, with 67 Y-STRs [7]. We found that their Y haplotypes were indeed identical at all these loci (Table S1 in the Supplemental Data).…”
Section: Resultsmentioning
confidence: 98%
“…We investigated a Chinese family carrying the DFNY1 Y-linked hearing-impairment mutation [6] and genotyped two family members, DFNY1-66 (affected) and DFNY1-101 (unaffected), who were separated by 13 generations, with 67 Y-STRs [7]. We found that their Y haplotypes were indeed identical at all these loci (Table S1 in the Supplemental Data).…”
Section: Resultsmentioning
confidence: 98%
“…However, reliable locus-specific mutation rates are needed to carefully choose loci to minimize the error rate in kinship analysis and sample identification 2 while obtaining the maximum discriminatory power (eg, Mulero et al, Lim et al and Vermeulen et al [3][4][5]. Also in population genetics and evolutionary studies, correct inferences on the timing of major demographic events, the age of the most common ancestor, as well as dating Y-lineages and tracing disease evolution are based on the knowledge of mutation rates (eg, Shi et al, Zerjal et al and Xue et al [6][7][8] ).…”
Section: Introductionmentioning
confidence: 99%
“…html). Up to now, reports on large volumes of population genetic data from a wide range of ethnic groups for the Y-STR loci have focused on the core loci [16][17][18][19], while several papers have reported polymorphic Y-STR loci other than the core loci [20][21][22].…”
Section: Introductionmentioning
confidence: 99%